Impact of Physical Activity Level on Whole-Body and Muscle-Cell Function in Older Adults - Hyo-Seong Yeo; Jae-Young Lim (Annals of Geriatric Medicine and Research, 2025)
Background The aim of this study was to examine the effects of different levels of physical activity on functional capacity, muscle strength, and the contractile properties of single muscle fibers in older adults. Methods Twenty-ones older adults (71.1±3.7 years) were divided into the high physical activity (HPA, n=10) and low physical activity (LPA, n=11) groups. Physical activity was assessed using a short form of the International Physical Activity Questionnaire (IPAQ). Physical function and muscle strength tests were performed. The fiber cross-sectional area (CSA), maximal force (Po), maximal force normalized to CSA (specific force, SF), maximal shortening velocity (Vo), and myosin heavy chain isoform expression were determined in single muscle fibers. Results IPAQ walking and total scores were higher in the HPA than in the LPA. The differences in body composition of the LPA and HPA were not significant. The 4-m walking velocity and isometric and isokinetic knee extensor strength were higher in the HPA than in the LPA. There was a significant difference between the two groups in Vo, but not fiber CSA, peak force, and SF. In addition, the Vo was significantly higher in the HPA than in the LPA for type I but not type II fibers. The correlation between total physical activity level and Vo was positive. Conclusion In older adults, higher levels of physical activity may have a greater impact on muscle function than on body composition. Moreover, increased physical activity is associated with higher Vo at the muscle cell level. Thus, we propose that enhancing overall physical activity levels should be considered an effective strategy for improving muscle function in older adults.